Evaluation of a model photo-caged dehydropeptide as a stimuli-responsive supramolecular hydrogel - Jervis, Peter John (2021)
Short peptides capped on the N-terminus with aromatic groups are often able to form supramolecular hydrogels, via self-assembly, in aqueous media. The rheological properties of these readily tunable hydrogels resemble those of the extracellular matrix (ECM) and therefore have potential for various biological applications, such as tissue engineering, biosensors, 3D bioprinting, drug delivery systems and wound dressings. We herein report a new photo-responsive supramolecular hydrogel based on a “caged” dehydropeptide (CNB-Phe-ΔPhe-OH 2), containing a photo-cleavable carboxy-2-nitrobenzyl (CNB) group. We have characterized this hydrogel using a range of techniques. Irradiation with UV light cleaves the pendant aromatic capping group, to liberate the corresponding uncaged model dehydropeptide (H-Phe-ΔPhe-OH 3), a process which was investigated by 1H NMR and HPLC studies. Crucially, this cleavage of the capping group is accompanied by dissolution of the hydrogel (studied visually and by fluorescence spectroscopy), as the delicate balance of intramolecular interactions within the hydrogel structure is disrupted. Hydrogels which can be disassembled non-invasively with temporal and spatial control have great potential for specialized on-demand drug release systems, wound dressing materials and various topical treatments. Both 2 and 3 were found to be non-cytotoxic to the human keratinocyte cell line, HaCaT. The UV-responsive hydrogel system reported here is complementary to previously reported related UV-responsive systems, which are generally composed of peptides formed from canonical amino acids, which are susceptible to enzymatic proteolysis in vivo. This system is based on a dehydrodipeptide structure which is known to confer proteolytic resistance. We have investigated the ability of the photo-activated system to accelerate the release of the antibiotic, ciprofloxacin, as well as some other small model drug compounds. We have also conducted some initial studies towards skin-related applications. Moreover, this model system could potentially be adapted for on-demand “self-delivery”, through the uncaging of known biologically active dehydrodipeptides.